2008
DOI: 10.1088/1751-8113/41/24/244002
|View full text |Cite
|
Sign up to set email alerts
|

The quantum brachistochrone problem for non-Hermitian Hamiltonians

Abstract: Recently Bender, Brody, Jones and Meister found that in the quantum brachistochrone problem the passage time needed for the evolution of certain initial states into specified final states can be made arbitrarily small, when the time-evolution operator is taken to be non-Hermitian but PTsymmetric. Here we demonstrate that such phenomena can also be obtained for non-Hermitian Hamiltonians for which PT -symmetry is completely broken, i.e. dissipative systems. We observe that the effect of a tunable passage time c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 26 publications
4
66
0
1
Order By: Relevance
“…The arbitrarily short alternative complex pathway from an up state to a down state, as illustrated by this thought experiment, is reminiscent of the short alternative distance between two widely separated space-time points as measured through a wormhole in general relativity. This comparison is of course controversial, and it has subsequently motivated much research and it has generated a lively debate in the literature [2,15,33,35,36,49,52,53,56]. We emphasise that the entire package of flipping the spin is not realised by a unitary operation.…”
Section: Extension Of Non-hermitian Hamiltonians To Higher-dimensmentioning
confidence: 96%
“…The arbitrarily short alternative complex pathway from an up state to a down state, as illustrated by this thought experiment, is reminiscent of the short alternative distance between two widely separated space-time points as measured through a wormhole in general relativity. This comparison is of course controversial, and it has subsequently motivated much research and it has generated a lively debate in the literature [2,15,33,35,36,49,52,53,56]. We emphasise that the entire package of flipping the spin is not realised by a unitary operation.…”
Section: Extension Of Non-hermitian Hamiltonians To Higher-dimensmentioning
confidence: 96%
“…However, Bender et al [2] have recently shown that for non-Hermitian PT -symmetric quantum systems, the answer is quite different and that the time evolution τ can be made arbitrarily small, despite the fact that the eigenvalue constraint is held fixed and identical to that for the corresponding Hermitian system. The mechanism described in [2] resembles the wormhole effect in general relativity and has generated discussion in the literature [6,7,8,9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The generic non-Hermitian quantum brachistochrone problem poses the same question, with the exception that now the evolution of the system is described by the nonHermitian Hamiltonian, which is not necessarily PT -symmetric [2,6,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations